Pengaruh keseimbangan kehidupan kerja terhadap kinerja melalui kepuasan kerja - Galuh Purwati Siti Mahmuda; Dwiarko Nugrohoseno (Universitas Negeri Surabaya, 2026)
This study aims to test and analyze the effect of work-life balance on job performance through job satisfaction in nurses at XYZ Hospital. This research is a quantitative study. The sampling technique used was saturated sampling, with 87 inpatient nurses as respondents. Statistical analysis in this study used the SEM-PLS method with the help of SmartPLS software version 3.0. The results of this study prove that work-life balance has a positive and significant effect on job performance, work-life balance has a positive and significant effect on job satisfaction, job satisfaction has a positive and significant effect on job performance, and job satisfaction mediates the effect of work-life balance on job performance. The implications of the results of this study indicate that the XYZ Hospital needs to pay attention to nurses’ time management to create a good work-life balance. In addition, the Hospital also needs to support efforts to improve nurses job satisfaction in order to have an impact on the resulting performance.